Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1039/c3ob40363g
|View full text |Cite
|
Sign up to set email alerts
|

First studies directed towards the diastereoselective synthesis of the BCD tricyclic core of brownin F

Abstract: The BCD tricyclic core of brownin F was prepared in eight synthetic operations for the first time. Our synthesis features a diastereo-, chemo-and regioselective intramolecular [3 + 2] cycloaddition between a cyclic carbonyl ylide and a γ-alkylidenebutenolide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Chouraqui and Commeiras recently demonstrated that spirocycles reminiscent of those found in the natural product brownin F could be rapidly accessed by oxidopyrylium cycloaddition chemistry (Scheme 53). 101 Brownin F was isolated in 1994 by Ohmoto from the wood of Harrisonia brownii , 102 and no total synthesis currently exists.…”
Section: Oxidopyrylium Cycloadditions In Total Synthesismentioning
confidence: 99%
“…Chouraqui and Commeiras recently demonstrated that spirocycles reminiscent of those found in the natural product brownin F could be rapidly accessed by oxidopyrylium cycloaddition chemistry (Scheme 53). 101 Brownin F was isolated in 1994 by Ohmoto from the wood of Harrisonia brownii , 102 and no total synthesis currently exists.…”
Section: Oxidopyrylium Cycloadditions In Total Synthesismentioning
confidence: 99%
“…The resulting solution was stirred for 30 min at ambient temperature, diluted with anhydrous Et 2 O (34 mL), and cooled to 0 °C. Aldehyde 1b (4.29 g, 17.9 mmol, 1.0 equiv) was added dropwise and the resulting solution was allowed to stir at 23 °C for 1 h at which point the reaction was quenched with sat. aq.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…8 Our initial investigations were sparked by the relative ease of separation of diastereomers (i.e., anti vs syn), straightforward differentiation utilizing 1 H NMR analysis (i.e., diagnostic protons α to ketone), and differing reactivity of each (vide infra). 13 A similar sequence was followed with 2,5disubstituted furan 1b 16 to give acetoxypyranone 2b (eq 2). Construction of substrates with heteroatom-containing tethers (i.e., oxygen 2c and nitrogen 2d) required alternative procedures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this context, the Lefebvre-type ring expansion of furyl alcohols was combined with pyrylium-alkene cycloadditions and applied in total synthesis routes towards complex natural products. [66][67][68] In 2010, the utility of this strategy was demonstrated by Nicolaou, Chen and co-workers who exploited an Achmatowicz/cycloaddition approach in the assembly of the bicyclic core structure of the sesquiterpenoid englerin A (Scheme 18…”
Section: Scheme 17 Ring Expansion/ketalization Pathway In the Assemblmentioning
confidence: 99%